Identification of intermittent transport in the scrape-off layer of MAST through high speed imaging. (August 2017) - Walkden, N.R.; Militello, F.; Harrison, J.; Farley, T.; Silburn, S.; Young, J.
Highlights: Pixel-wise statistical moments of high speed movies taken on MAST are used to infer the presence of filaments. Filaments observed in both single and double-null plasmas to propagate up to and beyond the ψ N = 1.5 poloidal flux surface. A quiescent region in the divertor volume is observed between the separatrix and the ψ N = 1.03 poloidal flux surface indicating a lack of coherent filaments in that region. The quiescent region coincides with a sharp rise in the integrated magnetic shear. Abstract: Using footage from high speed movies taken of the boundary plasma in the Mega Amp Spherical Tokamak (MAST) general properties of filaments are inferred through statistical moments. Filaments are observed up to and beyond the ψ N = 1.5 flux surface which, in single null configurations, lies well beyond the secondary separatrix and leads to filaments observed > 30 cm from the top of the plasma. In the divertor filaments are observed to connect through to the target, however a quiescent region is observed close to the X-point where no coherent filaments are identified. This region coincides with a sharp rise in the integrated magnetic shear which may change the nature of the filament cross-section.